Short-term health coaching on breast self-examination in adolescent girls: A Randomized Controlled Study - Indargairi Indargairi; Sintawati Sintawati; Fitri Afiati Nur; Nasywa Khaira Syukur; Imran Pashar (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Breast cancer remains the leading cancer among women globally, with increasing incidence in low- and middle-income countries. Despite improvements in adolescents’ knowledge of Breast Self-Examination (BSE), regular practice remains inconsistent. This study aimed to determine the effectiveness of BSE Calendar–based Health Coaching in improving knowledge, attitudes, and BSE behaviors among adolescent girls. Research Methodology: A randomized pretest–posttest control-group design was used with 96 female students (intervention n=50; control n=46) at a public secondary school in Makassar, Indonesia. The intervention group received three structured health coaching sessions combined with monthly self-monitoring using a BSE Calendar over three months, while the control group received conventional lecture-based education. Data were analyzed using the Wilcoxon signed-rank and Mann–Whitney U tests, followed by multivariate linear regression to adjust for baseline scores and covariates (α=0.05). Results: Post-intervention, the intervention group demonstrated significantly higher scores compared with the control group. Adjusted regression analysis showed significant effects on knowledge (β=1.21; 95% CI: 0.42–2.01; p=0.003), attitude (β=1.06; 95% CI: 0.45–1.67; p=0.001), and behavior (β=4.67; 95% CI: 3.02–6.31; p<0.001). Conclusion: BSE Calendar–based Health Coaching significantly enhances adolescents’ cognitive and behavioral preventive outcomes. Integrating structured coaching and self-monitoring tools into school-based health programs is recommended to strengthen early breast cancer detection strategies.